Teleworking and its Effect on SMEs in Barranquilla - Doria, Kelly Jonaha Gúzman; Ripoll, Javier Antaquera; Chamorro, Mónica Isabel Herazo; Ruíz, Liliana Álvarez; Rico, Julio Ordoñez (Journal of Ecohumanism, 2025)
Teleworking has experienced significant growth worldwide, changing the way companies operate and employees perform their tasks. Therefore, this research aims to analyse the effects of teleworking and its contribution to economic growth in the business development of SMEs in Barranquilla. The methodology of the research is quantitative-descriptive, where the instrument was a questionnaire of own design called "effects of telework and its contribution to economic growth in business development of SMEs" the study population were 78 entrepreneurs who run SMEs in the city. Among the results, it was found that half of the population (52.6%) of entrepreneurs have a positive perception of teleworking, however, after the pandemic, only 21.8% continued with teleworking, of which 100% consider that this form of work has had benefits in the development of the company. It can therefore be concluded that despite the positive perception of telework, there are significant challenges and opportunities in its implementation.